Education and Socialization of Understanding the Importance of Halal Food and Drinks for Elementary School Students: Pendidikan dan Sosialisasi Pemahaman Pentingnya Makanan dan Minuman Halal bagi Siswa Sekolah Dasar - Amin, Ageng Rayhan Al; Nasution, Ayu Niatasya; Faddila, Luthfiya; Putra, Nanda Nofaldi; Riswanto, Riswanto; Fatira, Marlya AK; Rahman, Abdul (Al Dzahab, 2025)
Purpose: This study aims to improve elementary school students' literacy regarding the consumption of halal food and drinks in the school environment and to establish it as a habit. Design/methodology/approach: This activity was conducted at SDT Al-Bukhari Muslim, located at Jl. Sriwijaya No. 57, Petisah Hulu Village, Medan Baru District, Medan City, North Sumatra. Data collection techniques included interviews with SDT Al-Bukhari Muslim representatives. The proposed solution is knowledge transfer to students through Educational Seminars and Socialization on the Importance of Halal Food and Drinks for Elementary School Students. Findings: The results indicate that the lack of students' understanding of the importance of consuming halal food and drinks was successfully addressed. Students' comprehension increased by 87% after educational and socialization activities on the importance of consuming halal food and drinks. Research implications: An educational program on halal food and drink consumption for SDT Al-Bukhari Muslim students can be implemented through a sustainable education and socialization program to enhance students' understanding of the importance of halal food and drinks.